Open Access to information: a right or an aspiration? (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Faced with the limitations in the use of the Internet in Latin America and Mexico, the economics and the controls related to copyright would have to be added to the situation. Although information technology services are developing programs that facilitates open access to information, they are not exempt from moral and legal conflicts, since user demand is very strong. In face of this situation, one must ask the question: is the right to information a right that we can all exercise to the full or is it a mere aspiration based on the declaration of a right? In the pre-digital or digital society, the right to information must include actions that will make the use of information a reality; the obligation to inform, the citizen's inherent right to be informed, and finally, the promotion of the use of information and reading. Keywords: Open Access. Latin America. Internet. Libraries. Copyright. Link para o texto completo (PDF)http://www.seer.ufrgs.br/index.php/EmQuestao/article/view/46183/31031